Adult T-cells impair neonatal cardiac regeneration. (14th April 2022) - Dolejsi, Theresa; Delgobo, Murilo; Schuetz, Thomas; Tortola, Luigi; Heinze, Katrin G; Hofmann, Ulrich; Frantz, Stefan; Bauer, Axel; Ruschitzka, Frank; Penninger, Josef M; Campos Ramos, Gustavo; Haubner, Bernhard J
Abstract: Aims: Newborn mice and humans display transient cardiac regenerative potential that rapidly declines postnatally. Patients who survive a myocardial infarction (MI) often develop chronic heart failure due to the heart's poor regeneration capacity. We hypothesized that the cardiac 'regenerative-to-scarring' transition might be driven by the perinatal shifts observed in the circulating T-cell compartment. Methods and results: Post-MI immune responses were characterized in 1- (P1) vs. 7-day-old (P7) mice subjected to left anterior descending artery ligation. Myocardial infarction induced robust early inflammatory responses (36 h post-MI) in both age groups, but neonatal hearts exhibited rapid resolution of inflammation and full functional recovery. The perinatal loss of myocardial regenerative capacity was paralleled by a baseline increase in αβ-T cell (CD4 + and CD8 + ) numbers. Strikingly, P1-infarcted mice reconstituted with adult T-cells shifted to an adult-like healing phenotype, marked by irreversible cardiac functional impairment and increased fibrosis. Infarcted neonatal mice harbouring adult T-cells also had more monocyte-derived macrophage recruitment, as typically seen in adults. At the transcriptome level, infarcted P1 hearts that received isolated adult T-cells showed enriched gene sets linked to fibrosis, inflammation, and interferon-gamma (IFN-γ) signalling. In contrast, newborn mice that received isolated Ifng –/– adult T-cells prior to MI displayed a regenerative phenotype that resembled that of its age-matched untreated controls. Conclusion: Physiological T-cell development or adoptive transfer of adult IFN-γ-producing T-cells into neonates contributed to impaired cardiac regeneration and promoted irreversible structural and functional cardiac damage. These findings reveal a trade-off between myocardial regenerative potential and the development of T-cell competence. Structured Graphical Abstract: Structured Graphical Abstract Schematic representation of T-cell involvement in the neonatal cardiac 'regenerative-to-scarring' transition. Cardiac regeneration following myocardial infarction in lymphophenic neonatal mice (upper panel). Adoptive adult T-cell transfer followed by myocardial infarction induced a sustained inflammatory response mainly via interferon-γ and monocyte derived macrophages (CCR2 + ) leading to impaired neonatal cardiac regeneration (lower panel).